LibQUAL+® and the Information Commons Initiative at Buffalo State College: 2003 to 2009 - Harvey, Eugene J.; Lindstrom, Maureen (Evidence Based Library and Information Practice, 2013)
Objective – To examine the effect of a transition to an information commons model of service organization on perceptions of library service quality. In 2003, the E. H. Butler Library at Buffalo State College began development of an Information Commons, which included moving the computing help desk to the library, reorganizing the physical units in the library around functional service areas, and moving the reference desk to the lobby. Methods – In 2003, 2006, and 2009, the library administered the LibQUAL+ survey, which measures the relationship between perceived library service delivery and library user satisfaction. The 2003 survey was conducted before the implementation of the Information Commons Initiative. Analyses of variance were conducted to compare the effect of the service changes on users’ perceptions of library service quality between the three data collection points, as well as to explore differences between undergraduate and graduate students. Results – The analyses revealed significant differences between the three data points, with significantly more positive perceptions of library service quality in 2006 and 2009 than in 2003. Comparisons between 2006 and 2009 were not statistically significant. In 2003, no significant differences were found between undergraduate and graduate students’ perceptions. However, in 2006, undergraduate students perceived higher levels of service quality after the development of the Information Commons than graduate students. This difference was maintained in 2009. Conclusion – The Information Commons has become a popular place for new programming, exhibits, workshops, and cultural events on campus. The library staff and administration have regained the respect of the campus community, as well as an appreciation for user-driven input and feedback and for ongoing assessment and evaluation.